Gallbladder perforation with cholecystopleural fistula: a case report - Garza-Báez, Pamela; Muñoz-Leija, David; Fernandez-Reyes, Bernardo A.; Quiroga-Garza, Alejandro; Negreros-Osuna, Adrian A. (International Surgery Journal, 2021)
The cholelithiasis is a common pathology, however, if left untreated may cause a gallbladder perforation (GBP). This complication can include local or generalized biliary spillage, or a fistulous communication to an adjacent organ. We report a case of a patient with cholecystopleural fistula in a 71-year-old male. Complicated cholelithiasis presented fistulous GBP into the right pleura cavity, progressing into an empyema. The diagnosis was made preoperatively with computed tomography, and the patient was treated with a laparoscopic cholecystectomy, thoracostomy tube, and a biliopleural fistulectomy. The postsurgical outcome was satisfactory, with uneventful follow-up 3 weeks after.